Development of an ethnobotany-based encyclopedia on the use of banana species by the Sambas Malay community - Andini Febrianti; Ari Sunandar; Mahwar Qurbaniah (Research and Development in Education (RaDEn), 2024)
The culture of the Sambas Malay community in using bananas must be upheld. Local wisdom could be preserved by employing educational resources. This study was aimed to develop an encyclopedia of banana species based on the ethnobotany of the utilization of the Malayu Sambas community which is used as a local wisdom-based learning resource and to determine the response given by students. In this study, the learning media to be developed is encyclopedia-based learning media because the encyclopedia is a form of print media that contains information and is accompanied by interesting illustrations according to the topics discussed. This research is designed to produce efficient learning materials and generate enthusiastic student feedback. Based on the ADDIE development model, this study used a five-stage process: analysis, design, development, implementation, and evaluation to conduct R&D. Data collection was based on interviews, observations, and questionnaires. Data were analyzed using a Likert questionnaire. Based on the assessment obtained, the refinement of the ethnobotany-based reference book of banana Species used by the Malay community in the Sambas area received high praise from the material expert (94.58%) and media expert (95.83%) as well as a huge response from the language expert (93.75%). Based on various factors such as content, language, usage, and appearance, 12 students provided affirmative responses, resulting in a 92.44% positivity rate in the small-scale trial, and 38 students gave positive answers of 91.96% in the large-scale experiment. The encyclopedia has been successfully compiled containing a QR code that provides information about the morphological characteristics of bananas and their uses in everyday life. Encyclopedia media can also be an educational tool that can maintain the existence of regional culture packaged using learning media.